Dramatic battles in eighteenth-century France - Connors, L (Voltaire Foundation, 2017)
The mid-eighteenth century witnessed a particularly intense conflict between the Enlightenment philosophes and their enemies, when intellectual and political confrontation became inseparable from a battle for public opinion. Logan J. Connors underscores the essential role that theatre played in these disputes. This is a fascinating and detailed study of the dramatic arm of France’s war of ideas in which the author examines how playwrights sought to win public support by controlling every aspect of theatrical production – from advertisements, to performances, to criticism. An expanding theatre-going public was recognised as both a force of influence and a force worth influencing. By analysing the most indicative examples of France’s polemical theatre of the period, Les Philosophes by Charles Palissot (1760) and Voltaire’s Le Café ou L’Ecossaise (1760), Connors explores the emergence of spectators as active agents in French society, and shows how theatre achieved an unrivalled status as a cultural weapon on the eve of the French Revolution. Adopting a holistic approach, Connors provides an original view of how theatre productions ‘worked’ under the ancien régime, and discusses how a specific polemical atmosphere in the eighteenth century gave rise to modern notions of reception and spectatorship. Acknowledgements List of illustrations Introduction: decision makers, doctes and theatre 1. Culture wars: philosphes and anti-philosophes in eighteenth-century France 2. The anatomy of a crime: polemics, pamphlets and preconditioning 3. A critical performance: Les Philosophes hits the boards 4. Parterre and balcony, spectator and reader: Palissot’s dramaturgical strategies 5. Pamphlets on the stage: Voltaire’s riposte philosophique 6. Spectators or readers? Voltaire’s ‘public’ concerns in L’Ecossaise 7. The affair continues: critical uncertainty in eighteenth-century France 8. (Re)Creating the event: performance criticism as intellectual war 9. Following the event: new definitions of theatre and criticism 10. Aftermath: theatre and polemics in pre-Revolutionary France Conclusion: le cri public Bibliography Index